RHEUMATOID ARTHRITIS IN WOMEN: CLINICAL FEATURES AND STAGES OF PROGRESSION (Лучшие интеллектуальные исследования, 2025)
Abstract: Rheumatoid arthritis (RA) is a chronic autoimmune disease that predominantly affects women, with a significantly higher prevalence compared to men. The disease is characterized by persistent joint inflammation, leading to pain, swelling, stiffness, and potential disability. The course of RA in women differs due to a combination of hormonal fluctuations, genetic predisposition, and lifestyle factors.